Associations of Suicide Risk and Community Integration Among Patients With Treatment-Resistant Depression - Huong, Pham Thi Thu; Wu, Chia-Yi; Lee, Ming-Been; Chen, I-Ming (Frontiers in Psychiatry, 2022)
Introduction: Treatment-resistant depression (TRD) is one of the primary causes of disability and major risk for suicide among patients living in the community. However, the suicide risks and care needs among patients with TRD during community reintegration process appeared to be unclear. This study aimed to investigate the association between community integration and suicide risks among this patient group with gender analysis. Methods: Patients diagnosed with major depressive disorder were recruited upon psychiatrists’ referral in two general hospitals in northern Taiwan during 2018 - 2019. The participants who experienced more than two failed treatments of antidepressants with partial remission were defined as TRD. A structured questionnaire was used to collect the socio-demographic, suicidality, and psychosocial information. Results: In a total of 125 participants, gender difference was found in certain community integration aspects such as home integration, productivity, and electronic social networking. The male participants appeared to have better involvement in social contact with internet but slightly less video link than females, while women had higher level of home integration in the past month. The participants who performed worse in the social integration and better home-based activity or productivity levels had higher suicide risks including suicide ideation and overall suicide risks. Conclusions: Community integration components of home, social and productivity were associated with suicidality in terms of overall suicide risk and recent suicide ideation. Facilitation of community integration regarding home and life arrangement might reduce suicide risks in TRD patients.